Konfidensial Kalam terhadap Jasa Pembuatan Tugas Kuliah dan Impaknya pada Karakter Mahasiswa (Kajian QS. Al Qashash Ayat 26) - Bachtiar Ahmad Fani Rangkuti (Program Pascasarjana Universitas Islam Negeri Sumatera utara, 2024)
The purpose of this study is to describe the argument of QS. Al Qashash Ayat 26 as a specificity to choose the right person in completing the work. And its impact on the character of students in completing assignments by using college assignment making services. This study uses a qualitative methodology type with an interpretation and social approach. The data collection technique used is the literature review technique by reviewing various scientific works related to the title. The analysis used in this article is content analysis to produce credible data. The results of this study found the sharia argument that allows students to seek convenience in completing college assignments. Related to its impact on the character of students, the use of college assignment making services can hinder the development of knowledge that should be obtained during the lecture process. Students who always rely on college assignment making services in completing their assignments, then students will not want to face competition in the outside world, especially in the world of work. In addition, dependence on college assignment making services can also increase the level of laziness so that students hesitate to do their own assignments and turn to assignment making services when facing difficulties.